Avoiding Routine Oxygen Therapy in Patients With Myocardial Infarction Saves Significant Expenditure for the Health Care System—Insights From the Randomized DETO2X-AMI Trial - Hofmann, Robin; Abebe, Tamrat Befekadu; Herlitz, Johan; James, Stefan K.; Erlinge, David; Alfredsson, Joakim; Jernberg, Tomas; Kellerth, Thomas; Ravn-Fischer, Annica; Lindahl, Bertil; Langenskiöld, Sophie, DETO2X-SWEDEHEART Investigators (Frontiers in Public Health, 2022)
BACKGROUND Myocardial infarction (MI) occurs frequently and requires considerable health care resources. It is important to ensure that the treatments which are provided are both clinically effective and economically justifiable. Based on recent new evidence, routine oxygen therapy is no longer recommended in MI patients without hypoxemia. By using data from a nationwide randomized clinical trial, we estimated oxygen therapy related cost savings in this important clinical setting. METHODS The DETermination of the role of Oxygen in suspected Acute Myocardial Infarction (DETO2X-AMI) trial randomized 6,629 patients from 35 hospitals across Sweden to oxygen at 6 L/min for 6-12 hours or ambient air. Costs for drug and medical supplies, and labor were calculated per patient, for the whole study population, and for the total annual care episodes for MI in Sweden (N=16,100) with 10 million inhabitants. RESULTS Per patient, costs were estimated to 36 USD, summing up to a total cost of 119,832 USD for the whole study population allocated to oxygen treatment. Applied to the annual care episodes for MI in Sweden, costs sum up to between 514,060 USD and 604,777 USD. In the trial, 62 (2%) patients assigned to oxygen and 254 (8%) patients assigned to ambient air developed hypoxemia. A threshold analysis suggested that up to a cut-off of 624 USD spent for hypoxemia treatment related costs per patient, avoiding routine oxygen therapy remains cost saving. CONCLUSIONS Avoiding routine oxygen therapy in patients with suspected or confirmed MI without hypoxemia at baseline saves significant expenditure for the health care system both with regards to medical and human resources.